2021
DOI: 10.1002/cyto.b.22038
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia andPNH‐type cells in bone marrow aspirates of myelodysplastic syndromes

Abstract: Background: Flow cytometry is increasingly applied in cytopenic patients suspected for myelodysplastic syndromes (MDS). Analysis includes evaluation of antigen expression patterns in granulocytes of which, for example, partial lack of CD16 may indicate dysplasia, but presence of paroxysmal nocturnal hemoglobinuria (PNH)-type cells should be considered. However, diagnostic bone marrow (BM) samples hamper PNH analysis because immature stages in the granulo-/monocytic compartment lack expression of certain glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Exact cut‐offs, if applied, are validated ‘in‐house’. A complete or partial loss of CD16 (a glycosyl‐phosphatidyl‐inositol [GPI] anchored protein, Figure 3 ) might suggest the presence of a paroxysmal nocturnal hemoglobinuria (PNH) clone which requires further testing for other GPI anchored antigens such as CD14 on mature monocytes and CD24 on mature neutrophils (Sutherland et al, 2018 ; Westers et al, 2021 ). Aged BM specimens, eosinophils contaminating the granulocyte gate and genetic polymorphisms may also account for changes in CD16 expression (de Haas et al, 1995 ; Loken et al, 2009 ; Stachurski et al, 2008 ).…”
Section: Maturing Granulocytic Compartmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Exact cut‐offs, if applied, are validated ‘in‐house’. A complete or partial loss of CD16 (a glycosyl‐phosphatidyl‐inositol [GPI] anchored protein, Figure 3 ) might suggest the presence of a paroxysmal nocturnal hemoglobinuria (PNH) clone which requires further testing for other GPI anchored antigens such as CD14 on mature monocytes and CD24 on mature neutrophils (Sutherland et al, 2018 ; Westers et al, 2021 ). Aged BM specimens, eosinophils contaminating the granulocyte gate and genetic polymorphisms may also account for changes in CD16 expression (de Haas et al, 1995 ; Loken et al, 2009 ; Stachurski et al, 2008 ).…”
Section: Maturing Granulocytic Compartmentmentioning
confidence: 99%
“…However, results of a survey concerning current MFC practice in 229 laboratories around the world showed that although many laboratories used large numbers of markers in MFC workup of MDS (median: 20 ± 4.5), the compliance with i MDSflow recommendations was low, and proposed scoring systems were not widely applied (Grille Montauban et al, 2019 ; Jensen et al, 2019 ). With the hope of increasing the harmonization of MFC MDS diagnostics, the current paper presents a summary of the progress in this field and an update on consensus i MDSFlow guidelines for the assessment of significant anomalies in various bone marrow (BM) cell compartments for MFC features of dysplasia as a part of a special Issue of Clinical Cytometry B, focused on MFC applications in MDS and MDS/MPN (Kern et al, 2022 ; van de Loosdrecht et al, 2023 ; van der Velden et al, 2023 ; Wagner‐Ballon et al, 2023 ; Westers et al, 2021 ; Westers et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…62,63,88,89 FC is also indicated for the identification of paroxysmal nocturnal hemoglobinuria clones. 90,91 Primary immunodeficiencies Although the definitive diagnosis of primary immunodeficiencies is generally ascertained by genetic analysis, FC is particularly helpful in the diagnosis of the following: (a) autoimmune lymphoproliferative syndrome, which is characterized by increased AQ11 AQ12 Box 6: What Is the Role of Genetic Testing: Which Genes, Methods, and Cell Source? What Is Its Position in the Diagnostic Algorithm?…”
Section: Myelodysplastic Neoplasmsmentioning
confidence: 99%
“…62,63,88,89 FC is also indicated for the identification of paroxysmal nocturnal hemoglobinuria clones. 90,91…”
Section: Diagnosismentioning
confidence: 99%
“…Further adding to their utility is the fact that CD34+ myeloid precursors tend to have a more stable immunophenotype in comparison to maturing cells and are less affected by reactive conditions or pre‐analytic factors. This contrasts with granulocytes and monocytes whose antigen expression and maturation patterns can be impacted by aging samples, sample hemodilution, reactive conditions, or the presence of a paroxysmal nocturnal hemoglobinuria (PNH) clone (van der Velden et al, 2023; Westers et al, 2021). In the appropriate clinical setting and appropriate sample quality control, however, the evaluation of maturing myelomonocytic and erythroid components provides valuable information especially in cases with limited number of CD34+ cells or cases with subtle phenotypic abnormalities in the CD34+ compartment.…”
mentioning
confidence: 99%